Level of Social Participation in the Creation of Urban Regeneration Programmes – The Case Study of Small Towns in Poland - Czupich, Mariusz (European Spatial Research and Policy, 2018)
Social participation enables citizens to take part in the decision-making process. It is an increasingly popular instrument in Poland. The effectiveness of participation is the most important issue in this context. In accordance with the Act of 9 October 2015, urban regeneration mainly applies to mitigating negative social phenomena. The social aspect is also important at the stage of establishing urban regeneration programmes. Extensive social participation in the process of creating these programmes is one of the main requirements. The aim of the article is to present the scale of the involvement of local communities in the procedure of creating regeneration programmes in selected small towns in Poland. Conclusions from the analysis include an assessment of participation success rate in regeneration activities.